Membangun Budaya Etika Bisnis: Studi Kasus Nestlé: Fostering A Culture of Business Ethics: A Case Study of Nestlé - Liem Gai Sin; Noor Fareen Abdul Rahim; Jocelyne Lee Jia Lin; Brahmmanand Sharma; Chanda Gulati; Hanis Zahira Binti Harmony Ghani; Gao Ming; Guo Yinuo; Hafisha Binti Mas Hassan; Andra Aprillia Ayu Triana; Yogita Pawar; Kamini Tomar; Kritika Mittal (Society, 2022)
Nestlé is one of the largest food companies in the world, with a presence in 191 countries and solid loyal customers. Nevertheless, a big organization like this cannot escape adverse ethical behavior in their company. Business ethics is the study of an organization’s corporate governance and initiatives related to corporate social responsibility. Businesses are morally obligated to give the public, stakeholders, customers, and the government the real worth of their money. Every firm engages in unethical practices for personal gain. This study aims to determine whether Nestlé will be able to survive in the long run if it is involved in unethical practices. Furthermore, this study intends to determine whether their involvement affects the customer’s purchase intention to buy their product. An online survey has been conducted to gather more information and provide evidence to support the conclusions. One hundred respondents from Malaysia, Indonesia, and India participated in this study. The analysis demonstrated that brand awareness, business ethics, and business ethics impact the intention of customers to buy Nestlé products. This study offers insightful information about how consumers view Nestlé, which could help them increase consumer trust in their brand.